Electromagnetic Field‐Responsive and Accurate Control of Bending in VO2 Based Micro‐Pillar Array. (22nd November 2022) - Zhang, Zhenhua; Zhao, Xiaodi; Zhang, Jian; Bai, Guohua; Guo, Hua; Liu, Weiwei; Zhang, Bin; Wang, Jin; Ji, Lianze; Chen, Fu‐rong; Zhao, Lizhong; Zhang, Xuefeng
Abstract: Electromagnetic field‐responsive mechanical deformation enables remote control of dynamic devices including micro‐robotic machines and smart surfaces. Metal–insulator transition (MIT) of vanadium dioxide (VO2 ) is developed for micro devices that are electrically or optically activated, but none of these is electromagnetic field‐responsive. Herein, a micro‐pillar array composed of epitaxial VO2 nanobeams that are asymmetrically coated with Cr, Au, and silicon oxide layers is demonstrated. Localized Joule heat, induced by the eddy current effect within the Cr or Au metal layer under an electromagnetic field, provides a high‐sensitive thermal response that triggers MIT of VO2, thus activates bending and relaxing of the micro‐pillars. For accurate and site‐specific control of the bending, layers of amorphous silicon oxide are added to the structure to endow tunable stiffness through electron beams‐matter interaction. These micro‐pillars are optimized to be a 2D, tractable surface on which directional transportation by remote control of the electromagnetic field in a liquid medium is realized. This discovery provides novel ideas for the design of electromagnetic field‐responsive structures. Abstract : VO2 ‐based micro‐pillar arrays are developed for a manipulating surface. Properties of the micro‐pillar arrays are designable by engineering their layered structures. A frequency magnetic field is the external stimuli to activate bending/relaxing of the micro‐pillars by eddy current. Directional particle transportation in a liquid environment is realized on the manipulation surface.